DEMYSTIFYING PRECIPITATION OF YOUTH VIOLENCE AND CRIMINAL BEHAVIOUR ON THE VICTIMS AND NIGERIAN SOCIETY: MIRRIORING THE DARK CLOUDS - Egbo, Ken; Akan, Kevin Akpanke; Owoseni, Joseph Sina (IJRDO - Journal of Social Science and Humanities Research, 2022)
Youth violence is one of the many problems facing the globe. The issue of youth violence and or crime has been declared as intolerable and catastrophic. The United Nations and the World Health organization have both agreed that effective planning and measures must be taken to guide and provide the youth a reasonable platform for a sustainable growth and development to take place. This study examined demystifying precipitation of youth violence and criminal behaviour on the victims and Nigerian society. The paper adopted the Gary Becker (1976) Rational Choice theory as its theoretical framework. The method of data collection were the quantitative (questionnaire) and qualitative (key informant interview). Eight hundred (800) Likert scale well- structured questionnaires were administered and retrieved while six (6) Key informant interviews were administered on participants across six states (one from each geopolitical zone). The quantitative instruments were analyzed with the aid of SPSS version 24 presented in simple percentages while the KII were analyzed using manual content analysis and ethnographic summaries. The findings revealed that youth violence and criminal behaviour are barbaric, illegal, destructive in nature and deadly. The study recommends that government must be determined to solve the problem of youth in general by engaging them in profitable venture. Crime prevention and control mechanism and security architecture of the country must be revamped. Individuals, families, NGOs, communities, local governments and states must be supportive of the federal government policies and laws to stem the twin problem of youth violence and criminal behaviour in the country. Youth guidance, reorientation, sensitization and conscientization should be periodic and more frequent to instill consciousness on them. This will reduce the menace to a greater extent. Youth must learn not to be readily available tools to be used by the self or someone in carrying out inhumane acts in Nigeria and beyond. Keywords: Trending, Patterns, Youth violence, crime, antisocial, deviant and criminal behaviour